Enhanced Anode Performance in Yeast Microbial Fuel Cells via Optimized Calcination of Eggshell Using Response Surface Method - Marcelinus Christwardana; Satrio Kuntolaksono; J. Joelianingsih; Achmad Yanuar Maulana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
This study aims to explore the potential of calcined eggshells as an economical and effective anode material in microbial fuel cells (MFCs). This research examines the enhancement of calcined eggshells as an anode material in MFCs by operating condition optimization using the Response Surface Method (RSM). The experimental findings underscore the substantial influence of temperature and the eggshell/NaOH ratio on voltage and maximum power density (MPD). Raising the calcination temperature from 550°C to 700°C improves both voltage and MPD, with peak performance seen at 700°C. Nonetheless, performance stabilizes above 850°C. The eggshell/NaOH ratio is significant, with enhancements seen at an optimum ratio of 4. ANOVA analysis indicates that the model accounts for 79.89% of the variability in voltage and 82.74% in MPD, while the modified R-squared values imply possible overfitting. Optimal calcination parameters (704.55°C and a ratio of 2.52) improve the microstructural characteristics of calcined eggshells and crystallinity, which are essential for electron transport and bacterial adhesion. SEM study indicates a morphological transition to a rough, porous structure, whilst XRD and FTIR investigations validate the conversion from calcium carbonate to calcium hydroxide, enhancing electrochemical characteristics. This study highlights the promise of optimized calcined eggshells as economical and effective materials for microbial fuel cells, advancing sustainable energy and materials science.